SAR405838: An optimized inhibitor of MDM2-p53 interaction that induces complete and durable tumor regression - Wang, Shaomeng (Cancer Res, 2014)
Blocking the MDM2-p53 protein-protein interaction has long been considered to offer a broad cancer therapeutic strategy, despite the potential risks of selecting tumors harboring p53 mutations that escape MDM2 control. In this study, we report a novel small molecule inhibitor of the MDM2-p53 interaction, SAR405838 (MI-77301) that has been advanced into Phase I clinical trials. SAR405838 binds to MDM2 with K(i) = 0.88 nM and has high specificity over other proteins. A co-crystal structure of the SAR405838:MDM2 complex shows that in addition to mimicking three key p53 amino acid residues, the inhibitor captures additional interactions not observed in the p53-MDM2 complex and induces refolding of the short, unstructured MDM2 N-terminal region to achieve its high affinity. SAR405838 effectively activates wild-type p53 in vitro and in xenograft tumor tissue of leukemia and solid tumors, leading to p53-dependent cell cycle arrest and/or apoptosis. At well-tolerated dose schedules, SAR405838 achieves either durable tumor regression or complete tumor growth inhibition in mouse xenograft models of SJSA-1 osteosarcoma, RS4;11 acute leukemia, LNCaP prostate cancer and HCT-116 colon cancer. Remarkably, a single oral dose of SAR405838 is sufficient to achieve complete tumor regression in the SJSA-1 model. Mechanistically, robust transcriptional up-regulation of PUMA induced by SAR405838 results in strong apoptosis in tumor tissue, leading to complete tumor regression. Our findings provide a preclinical basis upon which to evaluate SAR405838 as a therapeutic agent in patients whose tumors retain wild-type p53.